Awareness of the Bilingual «Angle of View» as an Independent Method in Modern Applied Linguistic Research (Proceedings of Southern Federal University. Philology, 2017)
REVIEWS Nikolaev S. (Pavlenko, Aneta. The Bilingual Mind: and What It Tells Us About Language and Thought. Cambridge University Press.